Pomalidomide, dexamethasone, and daratumumab in relapsed refractory multiple myeloma after lenalidomide treatment - Siegel, David S. (Leukemia, 2020)
Patients with multiple myeloma who have relapsed after or become refractory to lenalidomide in early treatment lines represent a clinically important population in need of effective therapies. The safety and efficacy of pomalidomide, low-dose dexamethasone, and daratumumab was evaluated in lenalidomide-pretreated patients with relapsed or refractory multiple myeloma (RRMM) after one to two prior treatment lines in the phase 2 MM-014 study. Patients received pomalidomide 4 mg daily from days 1–21 and dexamethasone 40 mg weekly (28-day cycles). Daratumumab 16 mg/kg was administered per label. Primary endpoint was overall response rate (ORR); secondary endpoints included progression-free survival (PFS) and safety. Per protocol, all patients (N = 112) had received lenalidomide in their most recent prior regimen (75.0% lenalidomide refractory). ORR was 77.7% (76.2% in lenalidomide-refractory patients); median follow-up was 17.2 months. Median PFS was not reached (1-year PFS rate 75.1%). The most common hematologic grade 3/4 treatment-emergent adverse event was neutropenia (62.5%). Grade 3/4 infections were reported in 31.3% of patients, including 13.4% with grade 3/4 pneumonia. These results demonstrate the safety and efficacy of pomalidomide-based therapy as early as second line in patients with RRMM, even immediately after lenalidomide failure, indicating that switching from the immunomodulatory agent class is not necessary.